Simulation of the seeding of equatorial spread F by circular gravity waves. Issue 1 (16th January 2013) - Krall, J.; Huba, J. D.; Joyce, G.; Hei, Matthew
<x xml:space="preserve">Abstract</x> [1] The Naval Research Laboratory three‐dimensional simulation code SAMI3/ESF is used to study the response of the postsunset ionosphere to circular gravity waves. We model the coupling of both circular (local) and plane wave (nonlocal) gravity waves to the bottomside F layer as a mechanism for triggering equatorial plasma bubbles. Results support the hypothesis that nonplane gravity waves can more strongly couple to the F layer than plane gravity waves. Results also show that the coupling of the seed wave to the F layer depends on the (nonlocal) growth rate and the local electron density at the position of the seed wave.